Kepemimpinan Hamba Tuhan Menurut Matius 20:25-28 - Hannas Hannas; Rinawaty Rinawaty (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2019)
Abstract: The leadership of God's servant raises a polemic because there are still those who think about God's servant being only servant and not being leader, however, in that opinion it is true. The researcher found a superior idea from Matthew 20:25-28 that placed God's servant not only as servant but also as leader. The method used in this research is the research developed by Walter C. Kaiser, Jr. in the book Towards Exegetical Theology: Biblical Exegesis for Teaching and Teaching, which addresses: contextual analysis, syntactic analysis, verbal analysis, theological analysis and homiletical analysis. The researchers, after observing the principle of exegesis presented by Kaiser, Jr., found that the text of Matthew 20: 25-28 could be discussed the themes of the leadership of God's servant who studied contextual and syntactical analysis providing support for the theme. Researchers also pay attention to verbal analysis, theological analysis and homiletical analysis, the results of which support the characteristics of God's servant leadership in Matthew 20:25-28, namely: communicative, assertive, gentle, humble, serving, willing to sacrifice.